Foreign Direct Investments in Poland against Countries of Visegrad Group - Lizińska, Wiesława; Danileviča, Alina; Idzikowska, Karolina (Olsztyn Economic Journal, 2022)
In the period of scarcity of investment capital, foreign direct investment (FDI) is an important source of its acquisition. These investments flow to the host countries in various conditions and consequences for the economy. The concept of linking the country’s position in terms of inflow and outflow of foreign direct investments with its economic development is the concept of the investment and development path – IDP (The Investment Development Path). The article diagnoses changes in the value of foreign direct investment in Poland against economies of Visegrad Group in 1995-2020, taking into account the effects of the pandemic on changes in FDI flows in 2016-2021. Against this background, the development of the Polish economy was diagnosed in the light of the path theory (IDP). The analysis covers the years 1995-2020 and 2016-2021 and uses data from UNCTAD and the World Bank. In the periods selected for the analysis, one can notice definitely different dynamics of changes in the value of FDI liabilities. The reaction of foreign investors in selected location markets varied during the pandemic. The diversification of the cumulative value of FDI receivables for individual countries is significant. During the pandemic, investors reacted to the situation in different ways. Among the selected countries, an increase in the value of FDI undertaken abroad was recorded in Slovakia and the Czech Republic. Polish investors and investors from Hungary made investments with lower values than in 2020. In all years, NOIP for Poland takes negative values, so the level of FDI undertaken in Poland exceeds the level of investments undertaken abroad. Identifying the transition to one of the most important stages on the IDP path – stage III is difficult. It is debatable to determine the period in which Poland entered such a stage. This results, among others, from low FDI. It is indicated that this is a period from 2004 to even 2013.